Предмет: Алгебра,
автор: deadrose123
1) х(х-4)=2+(х-1)^2
2) (х+2)(х-3)-3=(х+1)^2
3) у(5-у)=1-(у+3)^2
4) (у-1)^2-(у+1)(у-7)=0. помогите пожалуйста
Ответы
Автор ответа:
3
х2-4х=2+х2-2х+1
2х=-3
х=-1,5
х2-3х+2х-6-3=х2+2х+1
-3х=10
х=-3и 1/3
5у-у2=1-у2-6у-9
11у=-8
у=-8/11
у2-2у+1-у2+7у-у+7=0
4у=-8
у=-2
2х=-3
х=-1,5
х2-3х+2х-6-3=х2+2х+1
-3х=10
х=-3и 1/3
5у-у2=1-у2-6у-9
11у=-8
у=-8/11
у2-2у+1-у2+7у-у+7=0
4у=-8
у=-2
deadrose123:
спасибо
Похожие вопросы
Предмет: Математика,
автор: wanya121211
Предмет: Английский язык,
автор: nrajtemirova92
Предмет: Алгебра,
автор: homeworker67
Предмет: Математика,
автор: DilnazAskarova
Предмет: Математика,
автор: лерасупер123